2000
DOI: 10.1038/35018085
|View full text |Cite
|
Sign up to set email alerts
|

The segment polarity network is a robust developmental module

Abstract: All insects possess homologous segments, but segment specification differs radically among insect orders. In Drosophila, maternal morphogens control the patterned activation of gap genes, which encode transcriptional regulators that shape the patterned expression of pair-rule genes. This patterning cascade takes place before cellularization. Pair-rule gene products subsequently 'imprint' segment polarity genes with reiterated patterns, thus defining the primordial segments. This mechanism must be greatly modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
982
1
7

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,048 publications
(1,007 citation statements)
references
References 29 publications
17
982
1
7
Order By: Relevance
“…Other examples come from regulatory gene networks, such as the molecular network specifying fruit fly segments. Such networks may tolerate much quantitative variation in interactions among network genes [2][3][4][5] . Examples at the highest level of organization include macroscopic traits.…”
Section: Mutational Robustnessmentioning
confidence: 99%
“…Other examples come from regulatory gene networks, such as the molecular network specifying fruit fly segments. Such networks may tolerate much quantitative variation in interactions among network genes [2][3][4][5] . Examples at the highest level of organization include macroscopic traits.…”
Section: Mutational Robustnessmentioning
confidence: 99%
“…A series of recent modeling studies have made major strides towards identifying topological features of bionetworks that give rise to emergent properties such as the ability to sense and respond to environmental signals, maintain metabolic homeostasis, and form complex developmental patterns, all in a manner that is robust to environmental and genetic noise (Barkai and Leibler, 1997;Bhartiya et al, 2006;Brandman et al, 2005;Kollmann et al, 2005;Meir et al, 2002;Stelling et al, 2002;von Dassow et al, 2000;Wagner, 2005). A complement to understanding the topological features of bionetworks that lead to their qualitative properties is finding the precise parameter values which lead to specific quantitative phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Hunchback expression variability increased most significantly during a temperature reversal between 65 min and 100 min, indicating that this development period is the most critical for compensatory mechanism activity. Mathematically, von Dassow et al 28 demonstrated that the Drosophila segment polarity network is robust due to the intra-and inter-cellular topology of the system. To this end, an entire Drosophila protein-protein interaction map has been developed.…”
Section: Exploiting Microfluidic Flow For Unique Opportunities In Expmentioning
confidence: 99%